Муа arenaria L.— новый элемент в фауне Азовского моря - Савчук, М.Я. (Вестник зоологии, 1980)
Bivalve mollusk Муа arenaria L. was found for the first time in the Sea of Azov in the region of the Berdyansk spit southern part. The mollusk appearance here is supposed to be due to its larvae which left the lagoon in the Berdyansk spit head where in 1975 experiments with the Black Sea individuals of Л1. arenaria were carried out. Development of the new biocenosis will favour water purification, enrich fish food resources and permit this valuable mollusk to be utilized for human nutrition.